Potential effects of Polar Silk Road on the global foreland evolution of China’s coastal container ports - Peng, Yan; Du, Debin; Zhang, Xinfang; Wang, Xue (Frontiers in Marine Science, 2024)
The white paper on China’s Arctic Policy, which proposed the joint construction of the Polar Silk Road (PSR), was officially published in January 2018. As a short and economically feasible sea route, the PSR will inevitably affect the carrier’s market choice behaviour, thereby affecting the foreland network structure and foreland pattern of China’s coastal container ports (CCCP). Grasping the evolution trend of CCCP foreland under the PSR will help predict the development trend of the port and shipping market in advance and enable measures to be taken to adapt to the changing market environment. This paper constructs the port foreland network evolution (PFNE) model and presents a complex network delineation method of port foreland to simulate the effects of PSR on CCCP foreland evolution in different scenarios. Results show that the PSR’s addition to the CCCP foreland network will improve shipping connectivity, increase the connection between long-distance ports, reshape the clustering groups, promote the orderliness of the network and help the development of small and medium-sized ports. China’s global maritime transport pattern will change, which is mainly reflected in the enhanced shipping links between CCCP and Asia, Europe and Africa, while the importance of the Americas for CCCP weaken. PSR has a more obvious role in promoting the establishment of maritime links between China’s northern ports and the world ports. In the discussion, we propose the development policy of CCCP under the PSR.